Analysis of Public Interest on The participation of BPJS at Health Facility of First Level in Puskesmas Kebaman Banyuwangi 2018 - Sugeng Waluyo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The purpose of this study is to explore the interest of the community in the participation of BPJS in health centers including; Public perceptions about the Mandiri Health BPJS, Access and Types of services in the Puskesmas and Quality of services at the puskesmas are safe for BPJS Health participants. This type of research is qualitative research. Informants in this study were people in the puskesmas working area who did not have or had not participated in the BPJS. The informant taking method was purposive sampling. The numbers of informants in this study were nine informants. Data collection is done by in-depth interviews. Furthermore, the data were analyzed qualitatively by data credibility testing and source competing. The results of the study found that there were still many people who did not understand the term BPJS / Jamkesmas / KIS. Furthermore, the people also want the BPJS but for free, if they pay, most of the information is objected because of economic reasons. According to informants, access and service and service quality are quite good, but there are still problems with relatively difficult referral requests